Positive Childhood Experiences and Spiritual Well-Being: Psychological Flexibility and Meaning-Based Coping as Mediators in Turkish Sample - Maral, Sibel (Journal of religion and health, 2024)
Spiritual well-being enhances life quality, acts as a stress reliever, and mitigates unfavorable feelings. It helps individuals find meaning and purpose, increasing inner peace and happiness while improving stress management and overall well-being. This study examined whether positive childhood experiences are linked to spiritual well-being and if psychological flexibility and meaning-based coping serve as mediators. The sample included 1061 participants (Mage = 39.38; SD = 8.82) from various Turkish cities. Structural equation modeling assessed relationships between spiritual well-being, positive childhood experiences, psychological flexibility, and meaning-based coping. Results showed that positive childhood experiences directly enhance spiritual well-being, mediated by psychological flexibility and meaning-based coping. This underscores the significance of fostering positive childhood experiences to promote spiritual well-being and coping mechanisms.